PENGARUH PEMBELAJARAN INKUIRI SAINS BERBANTUAN KNOW, WANT, LEARN (KWL) TERHADAP HASIL BELAJAR KOGNITIF BIOLOGI SISWA KELAS XI MIA - Nanik Nurlaela; Hadi Suwono; Sueb Sueb (Graduate School of Universitas Negeri Malang, 2017)
This study aimed to describe the activity of students in learning and know the differences in cognitive learning outcomes of students in inquiry-science assisted KWL class with confirmatory class. The sampling technique was cluster sampling. The method used were nonrandomized pretest posttest control group design. Experimental class was taught using scientific inquiry model assisted KWL, and control classes taught using confirmatory models. Student activities were analyzed descriptively. Students activities demonstrate grade in learning implementation science inquiry assisted KWL showed 88.4% and confirmatory class showed 88.3%. Data analysis of the cognitive learning using Anacova with SPSS 22 for Windows that had previously been carried out tests of normality and homogeneity. The test results indicate that the F count Anacova generated at 64.619 in p. 0,000 <α (α = 0.05) means that there are differences in the cognitive learning classes taught using science inquiry learning assisted KWL model with confirmatory model with covariate effect on learning outcomes. The conclusions of this research that there are differences in cognitive achievement of students taught using scientific inquiry assisted KWL model with the students taught using confirmatory model with covariate effect on learning outcomes.Penelitian ini bertujuan untuk mendeskripsikan aktivitas siswa dalam pembelajaran dan mengetahui perbedaan hasil belajar kognitif siswa di kelas inkuiri sains berbantuan KWL dengan kelas konfirmatori. Teknik pengambilan sampel secara cluster sampling. Metode yang digunakan yaitu nonrandomized control group pretest posttest design. Kelas eksperimen diajar menggunakan model inkuiri sains berbantuan KWL, kelas kontrol diajar menggunakan model konfirmatori. Pelaksanaan pembelajaran kelas inkuiri sains berbantuan KWL menunjukkan sebesar 88,4% dan kelas konfirmatori sebasar 88,3%. Análisis data hasil belajar kognitif menggunakan anakova dengan bantuan SPSS 22.0 for Windows yang sebelumnya telah dilakukan uji normalitas dan homogenitas. Hasil uji anakova menunjukkan bahwa F hitung yang dihasilkan sebesar 64,619 dengan p. 0,000< α (α=0,05) artinya ada perbedaan hasil belajar kognitif kelas yang diajar menggunakan model pembelajaran inkuiri sains berbantuan KWL dengan model konfirmatori dengan kovariat berpengaruh terhadap hasil belajar (P<0,055). Simpulan penelitian ini yaitu ada perbedaan hasil belajar kognitif siswa yang diajar menggunakan model inkuiri sains berbantuan KWL dengan siswa yang diajar menggunakan model konfirmatori dengan variabel kovariat berpengaruh terhadap hasil belajar.